ChemInform Abstract: Rattling in the Quadruple Perovskite CuCu3V4O12. Issue 46 (November 2015) - Akizuki, Yasuhide; Yamada, Ikuya; Fujita, Koji; Taga, Kazuya; Kawakami, Takateru; Mizumaki, Masaichiro; Tanaka, Katsuhisa
Abstract A new A‐site‐ordered quadruple perovskite CuCu3V4O12 is obtained by a high‐pressure solid state reaction of a 2:12:3:5 molar mixture of Cu2O, CuO, V2O3, and V2O5, resp.